2017
DOI: 10.14569/ijacsa.2017.081019
|View full text |Cite
|
Sign up to set email alerts
|

The Ethical and Social Issues of Information Technology: A Case Study

Abstract: Abstract-The present study is conducted among 283 students from University of Zabol to identify the harm and ethical and social issues in the field of information technology and to classify the immoral practices that students are doing in this field. First various important issues in the field of IT in the social and ethical areas are discussed. Then the cases considered as the most commonly used immoral activities, are selected for evaluation, and the participants ranked these activities according to the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…Similar to the abovementioned analysis and the data in Table 5, the violation of Trademarks is average among the members of the IEEE Association [9].…”
Section: Checking the Achieved Results By Using A Single-sample T mentioning
confidence: 70%
See 4 more Smart Citations
“…Similar to the abovementioned analysis and the data in Table 5, the violation of Trademarks is average among the members of the IEEE Association [9].…”
Section: Checking the Achieved Results By Using A Single-sample T mentioning
confidence: 70%
“…For the Trade Secrets violation index, the mean value of the scores is 3.53, which is 0.53 units up than the value of 3, and the significance of the t-test at the 95% confidence level (Significance P < 0.05) indicates that the mean response of the individuals to the Trade Secrets violation component has a significant difference with the value of 3 and according to the 95% confidence interval, the mean response rate in the community with a 95% probability is within the range of 3.26-4.32. Since the questionnaire options are defined so that the responses indicating the violation of the Trade Secrets of others tend to the large numbers (Smaller than 3) it is concluded that the violation of Trade Secrets is low among the members of the IEEE Association because firstly, the mean response of individuals is up than 3 (to the " Strongly agree " or nonviolation of Trade Secrets), and secondly, the mean value is significant compared to the number 3 (Significance P < 0.05) [9].…”
Section: Checking the Achieved Results By Using A Single-sample T mentioning
confidence: 96%
See 3 more Smart Citations